The genome sequence of a carabid beetle, Abax parallelepipedus (Piller & Mitterpacher, 1783) [version 1; peer review: 2 approved] - Olga Sivell; Duncan Sivell; Ryan Mitchell; Maxwell V.L. Barclay (Wellcome Open Research)
We present a genome assembly from a female Abax parallelepipedus (carabid beetle; Arthropoda; Insecta; Coleoptera; Carabidae). The genome sequence has a total length of 596.99 megabases. Most of the assembly (97.3%) is scaffolded into 18 chromosomal pseudomolecules, including the X sex chromosome. The mitochondrial genome has also been assembled, with a length of 17.7 kilobases.